2022
DOI: 10.1128/mbio.01944-22
|View full text |Cite
|
Sign up to set email alerts
|

Human Nasal Organoids Model SARS-CoV-2 Upper Respiratory Infection and Recapitulate the Differential Infectivity of Emerging Variants

Abstract: An in vitro model of the nasal epithelium is imperative for understanding cell biology and virus-host interaction in the human upper respiratory tract. Here we report an organoid culture system of the nasal epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 50 publications
4
48
2
Order By: Relevance
“…In experimentally infected human bronchial epithelial cells, MAP3K19 expression was acutely up-regulated after SARS-CoV-2 infection but then progressively down-regulated compared to controls (Figure S9). Furthermore, the percentage of one of the cilium cell types (Figure 3A-B), ciliated cells (Ciliated), is signi cantly lower in critical COVID-19 patients than healthy controls (Figure 3A-D), in consistent with previous report that SARS-CoV-2 is able to deplete ciliated cells [27]. No difference in the distribution of other cell types was observed across patient groups.…”
Section: Resultssupporting
confidence: 90%
“…In experimentally infected human bronchial epithelial cells, MAP3K19 expression was acutely up-regulated after SARS-CoV-2 infection but then progressively down-regulated compared to controls (Figure S9). Furthermore, the percentage of one of the cilium cell types (Figure 3A-B), ciliated cells (Ciliated), is signi cantly lower in critical COVID-19 patients than healthy controls (Figure 3A-D), in consistent with previous report that SARS-CoV-2 is able to deplete ciliated cells [27]. No difference in the distribution of other cell types was observed across patient groups.…”
Section: Resultssupporting
confidence: 90%
“…Numerous studies showed the usefulness of organoid models in the evaluation of SARS-CoV-2 variants infectivity, such as using human airway, alveolar and intestinal organoid models to study the Alpha variant (B.1.1.7) [104] and nasal epithelium-derived organoid culture system to show high infectivity potential of the Omicron and Delta variants than in comparison with other VOC. [105]. Several mutations in SARS-CoV-2 variants target the S1 domain of the S protein, in addition to those already occurring in the RBD, which cause the affinity enhancement of the virus to the human ACE2 receptor and as a result, increase the transmissibility of the virus.…”
Section: Sars-cov-2 Variantsmentioning
confidence: 99%
“…As the primary target and entry portal of respiratory pathogens, nasal epithelial cells also express high levels of SARS-CoV-2 entry factors that favor robust SARS-CoV-2 replication, which constitutes the biological basis underlying viral pathogenesis and viral shedding ( 14 ). Thus, the measurement of viral replicative fitness in this organ could be a surrogate test for potential human spread.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the measurement of viral replicative fitness in this organ could be a surrogate test for potential human spread. Human nasal organoids were prepared as previously reported ( 14 ). Next, we examined SARS-CoV-2, BtCoV-WIV1, and PCoV-GX replication kinetics in nasal organoids derived from healthy donors.…”
Section: Resultsmentioning
confidence: 99%